Independensi, Akuntabilitas, Dan Transparansi: Kunci Efektivitas Fungsi Dan Tugas Bank Sentral - Eva Fa’izatul A’yun; Fatimatus Soleha; Rini Puji Astuti (Jurnal Ekonomi dan Bisnis Digital, 2025)
Bank The central bank is a key institution in maintaining the economic stability of a country. This article examines how the three key principles of independence, accountability and transparency are important pillars in improving the effectiveness of the central bank, and transparency are important pillars in improving the effectiveness of the central bank's implementation of the central bank's functions and duties. This research uses descriptive qualitative approach based on literature study to explore the relationship between these three principles and the governance of a credible and professional central bank. credible and professional central bank governance. The analysis shows that independence independence provides room for discretion for the central bank in policy making that is free from political intervention; accountability ensures public responsibility through reporting and oversight; while transparency through reporting and oversight; while transparency supports public understanding and policy predictability. and policy predictability. These three complement each other and form governance framework needed to respond effectively to the challenges of the modern economy effectively.